Characterization of Mental Health Care at a Basic Health Unit on Paraíba: A Documentary Study - Correia Firmino, Luan Cesar (2023)
The objective of the study was to describe the mental health care provided by the Family Health Strategy team in the rural area of the municipality of Imaculada-PB. This is documentary research with a quantitative approach carried out in a Basic Health Unit (UBS) in the rural area of the municipality of Imaculada-PB. The data source used was the Citizen's Electronic Record (PEC). The most frequent diagnoses were in the scope of anxiety and depressive disorders, and there were also other conditions such as epilepsy, schizophrenia and childhood autism. The identification of the most prevalent mental disorders is important to know the distribution and the main disorders that affect population groups, favoring the promotion and prevention of injuries.